Causal Model of the Association between Academic Burnout and Achievement Goals: The Intermediating Role of SelfEfficacy and Procrastination - Mohammad Hassan Seif; Ahmad Rastegar; Raheleh Ershadi; Saeed Mazloumian (Kerman University of Medical Sciences, 2016)
Background & Objective: There has been growing recognition that medical students interns residents and practicing physicians across many specialties are prone to burnout with recent studies linking high rates of burnout to adverse mental health issues The aim of this study was to examine factors affecting academic burnout among medical students and investigate the association between achievement goals and its dimensions academic selfefficacy and academic procrastination in the form of a causal model Methods: For this purpose 174 students (98 in the clinical stage and 76 in the preclinical stage) of Shiraz University of Medical Sciences (Iran) were selected based on Cochrans Formula and through simple random sampling The data collection tools consisted of the Maslach Burnout InventoryStudent Survey (MBISS) Achievement Goal Questionnaire (Elliot and McGregor) Academic SelfEfficacy Scale (Midgley et al) and Academic Procrastination Scale (Savari) To analyze the data path analysis and the Pearson correlation coefficient were used Results: The resulting path models indicated that academic burnout had significant negative relationships with mastery achievement goal performanceapproach and academic selfefficacy but it had significantly positive relationships with academic procrastination and performanceavoidance It was also found that achievement goals had impact on academic burnout through academic procrastination and selfefficacy The explained variance of academic burnout was 061 Conclusion: It was found that achievement goals and academic selfefficacy had significant effects on academic procrastination and burnout Thus it is suggested that those involved in education provide the students with situations in which they can achieve a higher sense of empowerment in learning so that they become more engaged in their academic work and be less likely to experience burnout